TORI'OU TRADITION IN THE TOLAKI TRIBE COMMUNITY PERSPECTIVE OF ISLAMIC LAW - Nurrahman, Panji; Melati, Friska Sukma; Haramain, Fathur Baldan (Hukum Islam, 2023)
This article aims to examine the tradition of tori'ou in the Tolaki tribe. The tori'ou tradition has been carried out for generations and until now it still causes debate because the tradition is considered a tradition that is contrary to Islamic law. Based on this problem, the author is interested in conducting research on the tori'ou tradition by formulating two problem formulations, namely; how is the practice of the tori'ou tradition carried out by the Tolaki tribe and how is the Islamic Law review of the tori'ou tradition. This research is a type of field research by conducting observations and interviews with Tolaki traditional leaders, religious leaders, and Tolaki community leaders. The data obtained was then analyzed using the Miles and Huberman model data analysis method. The results of this study indicate that the tori'ou tradition is a tradition of storing food in the last bed of a deceased person with the aim of remembering the deceased person by continuing to provide food. The tori'ou tradition is carried out from the first day after the person dies and continues until the 40th night or the 100th night.  While based on the review of Islamic Law, the tori'ou tradition is a form of 'Urf Fasid (damaged) because the Tolaki people's beliefs about the spirit are contrary to the teachings of Islamic law.